Evaluation of Compliance Using the DM E-Diary Application In patients with Diabetes Mellitus - Herman Priyono Luawo; Sri Susanti Papuke; Dirman Abdullah; Puspita Sukmawaty Rasyid; Yusni Podungge (Jambura Nursing Journal, 2023)
Diabetes Mellitus (DM) is a glucose metabolism disorder that causes problems in glucose control so that blood sugar levels become high. The main goal of DM treatment is to prevent and minimize acute and chronic complications. The increasing prevalence of DM sufferers and complications that occur due to DM and the lack of self-care abilities of patients indicate that DM is still a health problem. In general, this study aims to determine the evaluation of compliance with the use of the DM E-Diary application in patients with diabetes mellitus. This study describes the compliance of the results of the application of the DM E-Diary application in DM patients who are in the working area of the Bone Bolango Health Center by using a purposive sampling technique. The results showed that the majority of respondents were obedient in carrying out activities as many as 22 respondents (73.3%), while those who did not comply were as many as 8 respondents (26.7%). Patient self-management education and support is essential to prevent and reduce the risk of long-term complications. Diabetes cannot be generalized, but in general it can be said as a collection of overlapping anatomical and chemical problems with various factors. Physical activity increases insulin and lowers blood sugar levels. In general, it can be concluded that the application user is obedient in carrying out the schedule that has been programmed through the DM E-diary application.